2009
DOI: 10.1186/1756-9966-28-156
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of cenp-e in human hepatocellular carcinoma

Abstract: BackgroundCENP-E, one of spindle checkpoint proteins, plays a crucial role in the function of spindle checkpoint. Once CENP-E expression was interrupted, the chromosomes can not separate procedurally, and may result in aneuploidy which is a hallmark of most solid cancers, such as hepatocellular carcinoma (HCC). We investigate the expression of CENP-E in human hepatocellular carcinoma,. and analyze the effect of low CENP-E expression on chromosome separation in normal liver cell line (LO2).MethodsWe determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…These results are consistent with those of a previous study in which the silenced expression of KIF14 in pancreatic cancer cells resulted in increased anchorage-independent survival [43]. Apart from KIF14, many other cytokinesis regulators have also been reported as tumor suppressor genes, including KIF1A, KIF1B, KIF3, KIF4, KIF10, Von Hippel-Lindau syndrome protein (pVHL) and BRCA2 [16][18], [44][47]. Taken together, these results suggest that a KIF14 deficiency might promote aneuploidy, resulting in tumor formation, and that KIF14 might act as a tumor suppressor in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with those of a previous study in which the silenced expression of KIF14 in pancreatic cancer cells resulted in increased anchorage-independent survival [43]. Apart from KIF14, many other cytokinesis regulators have also been reported as tumor suppressor genes, including KIF1A, KIF1B, KIF3, KIF4, KIF10, Von Hippel-Lindau syndrome protein (pVHL) and BRCA2 [16][18], [44][47]. Taken together, these results suggest that a KIF14 deficiency might promote aneuploidy, resulting in tumor formation, and that KIF14 might act as a tumor suppressor in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Many components that regulate cytokinesis have been identified, and some molecules, including KIFs, have been clearly associated with cancer. For example, KIF2 and KIF15 have been identified as tumor antigens in breast cancer [12], [13]; KIF13A is overexpressed in some retinoblastomas [14]; KIF20A is up-regulated in pancreatic cancer [15]; KIF3 and KIF4 have been identified as tumor suppresser genes in gastric cancer [16], [17]; and the expression of KIF10 is reduced in hepatocellular carcinoma [18]. In addition, it has been reported that some KIF family members, including KIF3, KIF4 and KIF22, have conflicting roles in tumorigenesis [16], [17], [19][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CENP-E expression negatively correlated with disease-specific survival in patients with breast cancer [423]. In contrast, human hepatocellular carcinoma exhibits abnormally low levels of CENP-E [424]. Several non-synonymous single nucleotide polymorphisms were also reported in CENP-E and the Y63H point mutation, which disrupts the native conformation of the ATP-binding region in the CENP-E motor domain, was found to be associated with cancer [425].…”
Section: Consequences Of Abnormal Congressionmentioning
confidence: 99%
“…Microinjection of a CENP-E monoclonal antibody during prometaphase significantly delayed the onset of anaphase [18]. The reduced expression level of CENP-E has been observed in human hepatocellular carcinoma cases [19]. Here the expression level of CENP-E in human hepatic cell line L02 was higher than that in human hepatoma carcinoma cell line HepG2 during cell division phase suggesting the role in anti-tumour activity.…”
Section: Introductionmentioning
confidence: 81%